Penerapan Metode Amtsilati Dalam Penguasaan Kitab Kuning Di Pesantren Putri Al- Amanah Tambakberas Jombang - Bashirotul Hidayah (Muróbbî: Jurnal Ilmu Pendidikan, 2018)
Islamic boarding schools will not be separated from the mastery of the yellow book. To understand it, a method is needed, one of which is amtsilati. This study aims to determine the application of the method, the level of reading ability, and the constraints of the application of the amtsilati method in improving the ability to read the yellow book at the Al-Amanah Bahrul Ulum Islamic Boarding School. This research is a qualitative research. The data sources of this study are primary data & secondary data obtained from the Al-Amanah Bahrul Ulum Islamic boarding school. Data collection techniques used in this study were observation, interview and documentation. The data analysis used in this study is descriptive analysis, interpreting important data and then drawing conclusions from the results of understanding. The results of this study indicate that. First: The application of the amtsilati method in the study of the yellow book in the Al-Amanah Bahrul Ulum Islamic Boarding School includes: a) the process of implementing the dialogue method through certain steps and b) the book of amtsilati as a guidebook for mastering the yellow book. Second: The level of ability to read the yellow book at Al-Amanah Bahrul Ulum Islamic Boarding School includes: a) Santri begin to read yellow books skillfully, b) Know qowaid gradually, and c) Mastering Mufrodat. Third: Obstacles to the application of the amtsilati method in the Al-Amanah Bahrul Ulum Islamic Boarding School include: a) the educational background of santri, b) santri with low language skills, c) lack of support and participation, d) lack of vocabulary, e) environmental and residential factors f) inefficient time.